Grasslands feeling the heat: The effects of elevated temperatures on a subtropical grassland - Buhrmann, Rowan D.; Ramdhani, Syd; Pammenter, Norman W.; Naidoo, Sershen (African Biodiversity & Conservation, 2016)
Background: Tropical and subtropical Africa is predicted to experience a rise in temperature. The effects of rising temperatures on temperate grasslands have been studied using open-top chambers (OTCs) but reports for tropical/subtropical grasslands are scarce. This study used OTCs to investigate the effects of elevated temperatures on a threatened subtropical grassland type, namely KwaZulu-Natal Sandstone Sourveld (KZNSS). Objectives: To assess the effects of OTCs on selected abiotic parameters and plant productivity within KZNSS. Methods: Five OTC and control plots were randomly distributed at the same altitude within a patch of KZNSS. Air and soil temperature, relative humidity (RH), soil moisture content and light intensity were monitored in all plots in spring, summer, autumn and winter. Biomass production and plant density were measured in each season, for each life form (graminoid, forb and shrub), separately and combined. Results: The OTCs resulted in a rise in average, maximum and minimum day and night, air and soil temperatures. This increase, the degree of which differed across seasons, was accompanied by a decline in RH and soil moisture content. Elevated temperatures led to a significant increase in combined, graminoid and shrub above-ground productivity (AGP) and a decrease in forb density, but in certain seasons only. Below-ground biomass production was unaffected by elevated temperatures. Conclusions: OTCs can simulate realistic increases of air temperature in subtropical grasslands. Graminoids and shrubs appear to benefit from elevated temperatures whilst forbs decrease in abundance, possibly through competition and/or direct physiological effects.